2003
DOI: 10.1097/00004836-200301000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Fungemia After Saccharomyces boulardii Treatment in Immunocompromised Patients

Abstract: Saccharomyces cerevisiae is widely used as a probiotic compound. Clinical data suggest that this agent is safe and effective. We report two cases of fungemia caused by S. cerevisiae occurring in immunosuppressed patients treated orally with S. boulardii Molecular typing confirmed clonality in isolate strains from patients and the capsule. Physicians caring for immunosuppressed patients must be aware of this potential serious complication of probiotic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 23 publications
3
70
0
7
Order By: Relevance
“…However, such a strategy must be pursued with care: it has also been hypothesized that some degree of damage in CDI may be immune mediated, with decreased toxin-associated damage being seen in mice deficient in neutrophils, mast cells, or the inflammatory cytokine gamma interferon (IFN-␥) (194). Although live probiotics may have adverse effects in severely immunocompromised individuals (195,196), probiotic strains that are able to attenuate inflammatory responses in immunocompetent hosts may thus limit host-induced histological damage and improve disease symptoms. In order to identify optimal probiotics for the treatment of CDI, it will be crucial to identify those strains that are able to alleviate symptoms associated with deleterious inflammatory responses without undermining the ability to control C. difficile infection.…”
Section: Summary Of Potential Mechanisms Of Action Of Fmt Against CDImentioning
confidence: 99%
“…However, such a strategy must be pursued with care: it has also been hypothesized that some degree of damage in CDI may be immune mediated, with decreased toxin-associated damage being seen in mice deficient in neutrophils, mast cells, or the inflammatory cytokine gamma interferon (IFN-␥) (194). Although live probiotics may have adverse effects in severely immunocompromised individuals (195,196), probiotic strains that are able to attenuate inflammatory responses in immunocompetent hosts may thus limit host-induced histological damage and improve disease symptoms. In order to identify optimal probiotics for the treatment of CDI, it will be crucial to identify those strains that are able to alleviate symptoms associated with deleterious inflammatory responses without undermining the ability to control C. difficile infection.…”
Section: Summary Of Potential Mechanisms Of Action Of Fmt Against CDImentioning
confidence: 99%
“…In fact, S. cerevisiae has been described only recently as an "emerging infectious disease" [12,13]. S. cerevisiae has mostly been identified as a pathogen in critically ill patients who are immunocompromised [14,15] and in infants [16]. Not one single article could be found on an S. cerevisiae infection in an otherwise healthy, immuno-competent adult (Medline, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Probiotics are live organisms that provide health benefits and mostly include Lactobacillus species, Bifidobacterium species, Escherichia coli, Saccharomyces boulardii, and Trichuris suis (10,38,50,52,53). Although clinical trials of probiotics in some instances of dysbiosis have shown promising results, the efficacy of these live organisms appears to be quite limited and there is concern about occasional harmful side effects (3,5,43,46,57). 1 Prebiotics are defined as nondigestible food ingredients that promote the growth of bacteria, stimulate host immunity, prevent pathogenic infections, and facilitate host metabolism and mineral absorption (10,11,13,30,47,51,52).…”
mentioning
confidence: 99%